Особливості проведення аудиторської оцінки у процесі діагностики фінансового стану підприємств - Омелянчук, Т. М. (Видавництво Львівської політехніки, 2014)
Обґрунтовано, як аудит може впливати на якісний фінансовий аналіз поточного стану підприємства. Доведено доцільність використання аудиту як процедури підтвердження повноти фінансової звітності на початковому етапі комплексної оцінки фінансового стану суб’єкта господарювання, а також можливість застосування аудиторських процедур для діагностики достовірності результатів такої оцінки на її кінцевому етапі. It was established that none of the recent studies or publications does not raise the question of recognition of audit element integrated assessment of the financial condition of the company and as a debating something that is worth discussing in local reputable scientific circles. The concept of audit of the financial situation of the company in the current economic conditions is concretized. The role and importance of modern auditing for a full and accurate assessment of the financial condition of domestic enterprises is shown. The importance of the audit of the financial condition and results of an information providing important decision-making entities with an interest in the financial performance of the business entities is emphasized. In the article proved how audit can have an impact on the quality analysis of the current financial condition of the company. The expediency of the use of audit procedures as proof of completeness of financial statements in the initial phase of the complex evaluation of the financial condition of the entity, as well as the possibility of applying audit procedures for the diagnosis accuracy of the results of this assessment in its final stage is grounded. The directions on which it is advisable to audit the financial condition of the company, and the stages of analytical work, which should assess the financial condition of the entity are offered. It is proved that the audit process to assess the financial condition of the company increases its credibility and expanding areas of analysis that provides a diagnosis of the financial condition of the signs of consistency and comprehensiveness.
Peculiarities of auditor’s evaluation in the process of diagnosis enterprise’s financial condition
Keywords: підприємство; фінансовий стан; фінансовий аналіз; аудит; процедури; оцінювання; діагностика; enterprise; financial position; financial analysis; audit procedures; assessment; diagnosis